Minimum wage and global competitiveness of the South African textile industry - Moodley, Kiashan (My University, 2016)
ABSTRACT The South African Clothing and Textile Industry has been in a state of decline over the past fifteen years. Over this period, the industry has experienced numerous company closures and several job losses. A review of the literature found that although there is local demand for clothing, local manufacturers have been unable to compete with manufacturers based in China, Mauritius, India and Bangladesh, amongst other countries, with regard to price. These foreign-based manufacturers are generally able to manufacture and export clothing to South Africa, pay for shipping and import taxes, and still sell finished goods at a price that is lower than the local manufactures’ cost. Several authors have stated that the main reasons behind South African textile manufacturers’ not being able to compete with these imports is primarily due to high labour costs and low productivity. The World Economic Forum in their 2015-2016 Global Competitiveness Report too stated that the most problematic factor for doing business in South Africa is South Africa’s excessive and restrictive labour regulations. The literature also found that ex-South African based manufacturers have relocated to neighbouring countries, such as Lesotho and Swaziland, in order to capitalise on lower wage costs. After interviewing relevant stakeholders in the industry, this study found that in most cases, employers were non-compliant with the minimum wage regulation and were in fact paying employees bellow the legal minimum wage stipulation. Employers felt that the minimum wage value at the time was excessive and further felt that should they pay the minimum wage, they would not be able to compete with international manufacturers. Smaller manufacturers stated that not only would they be unable to compete with their international counterparts, they would not even be able to compete with larger local firms - should they comply and adhere to the minimum wage requirements. The research found that certain local manufacturers were at the time employing illegal immigrants from Malawi and Zimbabwe as opposed to South African citizens. The reasons for doing so were because Malawian and Zimbabwean workers accepted lower wages, were more skilled, worked faster and were willing to work longer hours than their South African counterparts.
MBA Thesis
Keywords: Textile industry, Minimum wage -- Economic aspects, Wages -- Textile workers -- South Africa.